Determinants of Organizational Commitment and Its Influence on Employee Performance at the Youth and Sports Service of South Tangerang City - Ikaputri, Mentari; Husainah, Nazifah; Haryoto, Cecep Yoto (Paradoks : Jurnal Ilmu Ekonomi, 2026)
This study investigates the roles of Emotional Intelligence and Spiritual Intelligence in enhancing Employee Performance in the Youth and Sports Office of South Tangerang City, with Organizational Commitment serving as the mediating variable.  Emotional Intelligence and Spiritual Intelligence act as independent factors, whilst Employee Performance is the dependent variable, with Organizational Commitment serving as the intermediary that links them.  Data were collected via questionnaires administered to 165 workers and evaluated using a quantitative methodology with an associative study design.  The investigation used Structural Equation Modeling (SEM) with the Partial Least Squares (SmartPLS) method.  The results indicate that Emotional Intelligence substantially enhances Organizational Commitment, shown by a coefficient of 0.262, and Spiritual Intelligence also has a notable positive effect with a value of 0.339.  Emotional Intelligence has a good direct influence on Employee Performance (0.199), while Spiritual Intelligence also considerably adds (0.235).  Organizational Commitment significantly impacts Employee Performance, with a correlation of 0.295.  The research indicates that both Emotional Intelligence and Spiritual Intelligence significantly improve Employee Performance when mediated by Organizational Commitment, as shown by coefficient values of 0.677 and 0.720, respectively.  These findings underscore the critical importance of corporate commitment in enhancing the impact of emotional and spiritual competencies on employee performance. The author also states that emotional and spiritual intelligence can help improve performance, job satisfaction, and public service, as well as build effective and ethical teams.